Deep Grouping Analysis of the Altered Cervical Canal Microbiota in Intrauterine Adhesion Patients - Hua, Xiangdong; Xu, Lu; Li, Qian; Zhang, Mi; Chen, Xiyi; Zhu, Yuan; Xu, Juan; Li, Jingyun (Reproductive sciences (Thousand Oaks, Calif.), 2022)
To deeply analyze the alterations of cervical canal microbiota in intrauterine adhesion (IUA) patients and microbiota’s relation to intrauterine adhesion (IUA) severity, we prospectively enrolled 23 consecutive patients diagnosed with mild-to-severe IUA and 8 women with infertility, 3 women with submucous myomas, or 8 women with endometrial polyps, but without IUA, as non_IUA subjects. For deep grouping analysis, these enrolled women were divided into six groups, two groups, and four groups respectively. Cervical mucus was drawn from the cervical canal of each participant. The bacterial composition was identified by 16S rDNA high-throughput sequencing. For analysis of six groups, mild IUA patients had similar cervical canal microbiota diversity and composition with submucous myomas patients. Compared with mild IUA participants, patients with moderate or severe IUA had a significantly lower diversity of bacteria and higher load of Firmicutes. For analysis of two groups, IUA patients had a significantly lower diversity of bacteria and higher load of Firmicutes than non_IUA subjects. KEGG pathway function analysis showed that metabolic pathways, biosynthesis of secondary metabolites, and microbial metabolism in diverse environments were mostly enriched for these cervical canal microbiota in all enrolled patients. The severity of IUA was associated with the altered abundance of phylum Firmicutes/Acinetobacteria or genus Lactobacillus/Gardnerella in the cervical canal. Higher bacterial load but less diversity in the cervical canal may be related with the severity of IUA. The function of these cervical canal microbiota were mostly involved in metabolic pathways.